Acquired ichthyosiform-like erythroderma with lichenoid tissue reaction in a child. - Miteva, L. (European Journal of Pediatric Dermatology, 2003)
A 9-year-old boy developed erythroderma and hyperkeratotic plaques on the trunk and the extremities. Light-microscopic studies showed a lichenoid tissue reaction. The course of the disease was characterized by chronicity and partial response to systemic steroids. The differential diagnosis of this unique condition associating acquired ichthyosiform-like erythroderma and lichenoid tissue reaction is discussed. Based on these clinical and histological findings in the present patient lichen planus, graft-versus-host disease, lichenoid drug eruption, keratosis lichenoides chronica, lupus erythematosus, lymphoma, ichthyosiform erythroderma and Netherton’s syndrome should be considered. None of these is consistent with the features of our case. Similar clinical and histological features of the condition have been described in another case report from the literature, suggesting it may represent an unusual form of ichthyosiform erythroderma or possibly a new entity.